"A language is a mentality": A narrative, positive-psychological view of six learners' development of bilingualism. (December 2015) - Oxford, Rebecca L.; Pacheco Acuña, Gilda; Solís Hernández, Mayra; Smith, Andrew L.
Abstract: This article focuses on bilingualism in light of positive psychology, which involves well-being and deals with human difficulties from the vantage point of strength rather than weakness. Based on in-depth narratives of six bilingual individuals, a number of interrelated themes arose: bilingual identity, emotions, peak experiences, motivation, hope, resilience, hardiness (existential courage), and learning strategies. The article helps elucidate processes by which individuals become bilingual, discusses ways to optimize positive psychology research, and provides implications for teaching.